2018
DOI: 10.1021/acs.joc.8b01868
|View full text |Cite
|
Sign up to set email alerts
|

Iminium Ion and N-Hydroxyimide as the Surrogate Components in DEAD-Promoted Oxidative Ugi Variant

Abstract: A practical metal-free oxidative Ugi-type three-component assembly has been achieved efficiently, employing a tertiary-amine-derived iminium ion as an imine surrogate, N-hydroxyimide as an acid surrogate, and DEAD as an oxidant. This dual-surrogate Ugi variant proceeded with a broad substrate scope and desired functional group tolerance, leading to a wide range of N-alkyl-N-acyl amino­phthalimide and N-alkyl-N-acylamino­succinimide derivatives in good isolated yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Zhen et al developed an innovative strategy for the synthesis of N -alkyl- N -acylaminophthalimide 162a and N -alkyl- N -acylaminosuccinimide 162b through metal-free oxidative JUS-3CR by employing tertiary amine 159 as an imine surrogate, N -hydroxyimide 160 as an acid surrogate, isocyanides 5 , and DEAD 161 as an oxidant (Scheme ). This approach contains a broad substrate scope and desired functional group tolerance, which leads to an extensive range of N -alkyl- N -acylaminophthalimide 162a and N -alkyl- N -acylaminosuccinimide 162b derivatives in good yields.…”
Section: Cyclic Imines In Joulliè−ugi Reactionmentioning
confidence: 99%
“…Zhen et al developed an innovative strategy for the synthesis of N -alkyl- N -acylaminophthalimide 162a and N -alkyl- N -acylaminosuccinimide 162b through metal-free oxidative JUS-3CR by employing tertiary amine 159 as an imine surrogate, N -hydroxyimide 160 as an acid surrogate, isocyanides 5 , and DEAD 161 as an oxidant (Scheme ). This approach contains a broad substrate scope and desired functional group tolerance, which leads to an extensive range of N -alkyl- N -acylaminophthalimide 162a and N -alkyl- N -acylaminosuccinimide 162b derivatives in good yields.…”
Section: Cyclic Imines In Joulliè−ugi Reactionmentioning
confidence: 99%
“…Quite recently, our group explored two types of DEADpromoted oxidative Ugi-type reactions of tertiary amines. 16,17 We have been committed to broadening the application range of DEAD-assisted oxidations, which prompted us to explore the [3 + 2] cycloaddition-based synthesis of pyrrolo [2,1a]isoquinoline.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Same research group further developed a novel DEAD promoted oxidative Ugi-type reaction where imine surrogates and acid surrogates were employed for the transformation. [35] N-Phenyl tetrahydroisoquinolines were used as imine surrogates and N-hydroxyphthalimide (NHPI) or N-hydroxysuccinimide (NHS) were utilized as acid surrogates (Scheme 14). The optimization studies revealed that the dual-surrogate Ugi-type reaction occurred smoothly in chlorinated solvents at room temperature.…”
Section: Oxidative Ugi-type Reactionsmentioning
confidence: 99%